'Meer nomenclature' and the description of order in The Garden of Cyrus. Issue 2 (April 2014) - Preston, Claire
<x xml:space="preserve">Abstract</x> The developing scientific culture of the seventeenth century demanded an augmented lexical range in English that was supplied by natural philosophers and savants like Thomas Browne, Robert Boyle, and John Evelyn, whose humanist linguistic training qualified them to introduce learned neologisms. At the same time, they were engaged in ongoing debates about the propriety of semantic and rhetorical embellishment in the writing of science. This essay considers the nature of neologism and lexical extension more generally in a range of work by a number of natural philosophers, natural historians, and georgic writers, with special attention to Browne himself – perhaps the most fluent scientific neologizer of the early modern period – and to The Garden of Cyrus (1658), a work inflected by his natural history and exemplifying some solutions to the terminological needs of early modern science.